Integrasi Nilai-Nilai Pendidikan Islam dalam Hidup Rukun Bermasyarakat pada Mata Pelajaran PPKn Kelas Dasar - Amirullah; Afifah Handiar; Rahma Aulia Azzahra (Indonesian Journal of Islamic Education Studies (INJURIES), 2023)
The purpose of the research that we have done is to inform the correct ways of implementation in the efforts of national unity related to Islamic values in living in harmony in society in Civics subjects at level II Elementary School level. The implementation of this research uses a library method with the hope of obtaining data that can be comprehensive and in-depth. From this research has a conclusion with the integration of various Islamic values in education so that it can make students do various valuable and useful activities. It can be seen that PPKn contains the value of nationalism (nationality), religious material, unity material and social values. It is expected that in living in harmony with society in Civics subjects, the incorporation or renewal of the integration of useful Islamic values will be able to make students have morals and carry out activities that are useful and valuable for the surrounding community. Keywords: Islamic Education Values; Living in Harmony with Society; PPKn Lessons.